Rhabdomyolysis in polytraumatized critically Ill patients in ICU : Diagnosis & managment - Ayat Ahmed Sadek Aly; Khaled Hussin; Mahmoud Mohammed Kenawi; Sally Salah Eldin Mohammed (Cairo : Ayat Ahmed Sadek Aly, 2017)
Background: The trauma patient sustains numerous potentially harmful insults that may contribute to a notable risk of acute kidney injury (AKI). The aim of this study was to investigate the incidence of rabdomyolysis and AKI in severely injured trauma patients admitted to the intensive care unit (ICU). Methods: polyTrauma patients (ISSadmitted to the ICU for at least 72 hours at El-Helal trauma center and Kasr El-einy university hospital were included. The outcome measure was AKI diagnosed according to RIFLE criteria in day 1, 2 and 3 in the ICU. Results: Our study revealed that 52.6% of polytraumatized patients who were included developed rhabdomyolysis. 24% of our patient population developed AKI, All these patients were diagnosed to have rhabdomyolysis. AKI group showed higher levels of CK during the follow up period, cut off values of CK in relation to AKI were >1385U/L, >3114U/L and >1723U/L respectively. 20% of our patient population died. Conclusion: AKI in ICU-admitted trauma patients is a common complication with substantial mortality
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Critical Care Medicine
Issued also as CD
Keywords: Acute kidney injury; Rhabdomyolysis; Trauma